2019
DOI: 10.1093/ndt/gfz066
|View full text |Cite
|
Sign up to set email alerts
|

The utility of magnetic resonance imaging for noninvasive evaluation of diabetic nephropathy

Abstract: Background Noninvasive quantitative measurement of fibrosis in chronic kidney disease (CKD) would be desirable diagnostically and therapeutically but standard radiologic imaging is too variable for clinical usage. By applying a vibratory force, tissue shear wave stiffness can be measured by magnetic resonance elastography (MRE) that may correlate with progression of kidney fibrosis. Since decreased kidney perfusion decreases tissue turgor and stiffness, we combined newly available three-dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 42 publications
0
31
0
Order By: Relevance
“…Most of the data from transplanted kidneys showed that MRE values were negatively associated with eGFR and fibrosis burden. Nevertheless, as authors from recent studies suggested, to our surprise, differing from that in the liver and allografts, MRE shear stiffness decreases with worsening CKD in IgA nephropathy [15], lupus nephritis [16], and diabetic nephropathy [17]. In IgA nephropathy, which is the most commonly studied glomerular nephritis, although 16 patients with biopsy-proven IgAN were studied, the investigators found that advanced stage IgAN was associated with renal softening and restricted water diffusion [15].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Most of the data from transplanted kidneys showed that MRE values were negatively associated with eGFR and fibrosis burden. Nevertheless, as authors from recent studies suggested, to our surprise, differing from that in the liver and allografts, MRE shear stiffness decreases with worsening CKD in IgA nephropathy [15], lupus nephritis [16], and diabetic nephropathy [17]. In IgA nephropathy, which is the most commonly studied glomerular nephritis, although 16 patients with biopsy-proven IgAN were studied, the investigators found that advanced stage IgAN was associated with renal softening and restricted water diffusion [15].…”
Section: Discussionmentioning
confidence: 98%
“…MRE combines imaging with the assessment of acoustic waves for the quantitative determination of the viscoelastic properties of tissues based on their response to external mechanical vibrations [29]. To date, MRE is a well-established technique for liver fibrosis imaging [30-32]; however, there are only a few high-quality studies evaluating MRE in human kidney allografts [8, 10, 33] and in native kidneys [9, 15-17]. The kidney possesses specific features rendering it more difficult to image since it is a heterogeneous organ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MRI is an emerging noninvasive tool to assess kidney fibrosis in diabetic disease. 10 Ultrasound failed as a noninvasive tool because renal size, cortical thickness and cortical echogenicity are preserved until ESRD occurs. 11 In addition, ultrasound findings are operatordependent, and the renal volume is significantly affected by the degree of hydration at the time of examination.…”
Section: Discussionmentioning
confidence: 99%
“…This result was supported by a significant correlation between RBF and GFR, estimated by creatinine and cystatin-C. Other studies have shown similar results. Recently, Brown et al analyzed in a pilot study the ability of ASL to provide information on fibrotic changes occurring during DKD [51]. To do so, they studied diabetic subjects from early to advanced categories of kidney disease and compared them with healthy volunteers using magnetic resonance elastography and ASL.…”
Section: Magnetic Resonance Imaging and Clinical Utilitymentioning
confidence: 99%